1999
DOI: 10.1128/aac.43.9.2236
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of BMS-207147 against Over 600 Contemporary Clinical Bloodstream Isolates of Candida Species from the SENTRY Antimicrobial Surveillance Program in North America and Latin America

Abstract: We compared the in vitro activity of BMS-207147, an investigational triazole, with those of itraconazole and fluconazole against 613 clinical bloodstream isolates of Candida spp. collected from SENTRY participating hospitals during 1997 and 1998. Overall, BMS-207147 was the most active azole against all Candidaspp. While both BMS-207147 and itraconazole displayed a stepwise decrease in activity against isolates for which the fluconazole MICs were elevated, BMS-207147 had two- to fourfold greater activity than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Ravuconazole is a broad-spectrum triazole that showed activity against a wide array of fungal species including Aspergillus spp., Candida spp., and Cryptococcus neoformans [9], [10]. Studies have shown that the efficacy of this new triazole was comparable to that of posaconazole and voriconazole [9], [10], [11]. In addition to antifungal activity, ravuconazole also showed in vitro activity against the parasite Trypanosoma cruzi, the causative agent of Chagas disease, another neglected tropical disease on the WHO list [12].…”
Section: Introductionmentioning
confidence: 96%
“…Ravuconazole is a broad-spectrum triazole that showed activity against a wide array of fungal species including Aspergillus spp., Candida spp., and Cryptococcus neoformans [9], [10]. Studies have shown that the efficacy of this new triazole was comparable to that of posaconazole and voriconazole [9], [10], [11]. In addition to antifungal activity, ravuconazole also showed in vitro activity against the parasite Trypanosoma cruzi, the causative agent of Chagas disease, another neglected tropical disease on the WHO list [12].…”
Section: Introductionmentioning
confidence: 96%
“…Major Fairchild et al [8] Nolla-Salas et al [9] Saiman et al [10] Swoboda et al [11] Tortorano et al [12] Trick et al [2] Period studied 1992-1998 1993-1995 1991-1998 1991-1992 1993-1995 1990-2002 1983-2002 1989-1999 [19,20]. In this programme, the authors also demonstrated large variations within the same country.…”
Section: Variability Of Clinical Specimensmentioning
confidence: 77%
“…Tortorano et al collected all Candida infections in the medicosurgical ICU in one hospital [12]. Among the 58 strains tested, all C. albicans strains (n = 19) were susceptible to all of the drugs evaluated. Among the C. glabrata strains (n = 39), the authors reported an increase in the MIC of fluconazole from 1 g/mL to 32 g/mL during treatment with 400 mg/day for 10 days in one patient.…”
Section: Prevalence Of Resistancementioning
confidence: 99%
“…All of the new triazoles have excellent in vitro activity against a wide variety of fungal pathogens ( Table 1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] provide similar evidence that these agents will be effective. 17,18 In vitro studies indicate that the agents also may be effective in treating infections caused by Cryptococcus sp.…”
Section: Triazolesmentioning
confidence: 87%